Role of Universities in Promoting Innovation Policy in Southeast Asian Countries - Asmara, Anugerah Yuka (National Research and Innovation Agency, Indonesia, 2023)
Universities have been widely acknowledged as knowledge producers contributing to innovation practice in many countries. They play main role in doing research and development (R&D) activities and then commercializing outputs of R&D to market. In addition, role of university is also as producer of knowledge for innovation policy. Notwithstanding, the role of university in promoting innovation policy is rarely founded in scientific publications. This study is aimed to explain role of university in promoting innovation policy by comparing three countries in Southeast Asia namely, Thailand, Malaysia, and Indonesia. Three countries were called as the “Asian Tiger” in 1960s, but they have different economic growth currently. Literature studies are main data sources used to this study. Also, the post-positivistic approach and descriptive analysis technique are part of this research method. The study finding that Thailand and Malaysia have specific study course of innovation policy at universities. They have contributed to promote innovation policy at both countries.Keywords: Role, Universities, Innovation, Policy, Southeast Asia